Penerapan PSAK 109 Tentang Pelaporan Keuangan Akuntansi Zakat, Infak/Sedekah Pada BAZNAS - Ridho, Ali; Rofiq, Muhammad (LITERATUS, 2024)
The main factor causing the failure to achieve the potential for receiving zakat, infaq and alms in zakat management institutions is the lack of public trust in the management institutions, so that guidelines for preparing financial reports are needed, namely PSAK No. 109 concerning accounting for zakat, infaq/alms. The purpose of this study is to reconstruct the financial report of zakat, infak/alms at the National Zakat Agency (BAZNAS), which can then be seen how the financial report is made by BAZNAS. This study uses a descriptive method which is carried out through observation, data collection and direct interviews with the Head of BAZNAS. This study is intended to look at the concepts of recognition, measurement, presentation and disclosure that occur at the National Zakat Agency, and to provide an overview of the financial report of zakat, infak/alms, which then analyzes the conformity of the financial report of zakat, infak/alms at BAZNAS with the applicable standards, namely PSAK No. 109. The results of this study indicate that transparency and accountability in the financial reports of zakat, infak/alms at BAZNAS have been carried out and analyzed based on PSAK No. 109, which consists of five components of financial reports, namely, financial position report, fund change report, managed asset change report, cash flow report, and notes to the financial reports. The National Zakat Agency has been proven to have carried out the bookkeeping process in accordance with the accounting concept in PSAK Number 109 in terms of recognition, measurement, presentation and disclosure.